(untitled) (Scientia Agropecuaria, 2020)
Flower production is an important item in the Ecuadorian economy, but intensive monoculture systems of species such as Gypsophila paniculata cause alterations in the soil. The objective was to evaluate the effect of the incorporation of organic amendments in the form of compost and vermicompost in the Gypsophila monoculture soil. A trial was considered under greenhouse conditions, with a completely randomized design (CRD) with nine treatments. Gypsophila was planted in pots with Gypsophila production soil from Ecuador to which compost and vermicompost doses were added to evaluate three harvest cycles. Foliar absorption and fresh weight of green matter were determined. After harvest 1 and harvest 3, the soil substrate was characterized. The incorporation of compost or vermicompost compared to the Control treatment, improves the foliar absorption of phosphorus, potassium, magnesium and sulfur in the three harvests, in the soil substrate the Electrical Conductivity (EC), the available phosphorus and the content of Organic Matter (OM), there is a buffer effect on the pH and the bulk density decreases. The fresh weight values of stems from treatments with organic amendments are higher than the Control in the three harvests.